Correlation of salivary and gastric acid secretions in duodenal ulcer patients in tropics. Issue 7 (July 1979) - Nagwani, P. L.; Naik, S. R.; Sachdev, S.; Srivastava, P. N.; Chuttani, H. K.
Abstract : Salivary flow rates on mechanical stimulation by forced spitting method and by chemical stimulation with 10% citric acid and gastric acidity using an augmented histamine test were determined in 20 adult patients suffering from duodenal ulcer and in 20 adult control subjects matched with respect to age, sex, and body weight. Salivary flow rates were found to be much higher in response to chemical than to mechanical stimulus in both the groups. Duodenal ulcer patients exhibited an unexplained exaggerated response to chemical stimulation. Salivary pH, amylase, sodium, and potassium levels showed no significant differences between the two groups. The flow rates by either method generally showed a positive correlation with body weight in both the groups. Histamine stimulated gastric acid secretion was higher in duodenal ulcer patients than in controls. Acid secretion did not appear to be related to weight and also showed no consistent correlation with the salivary flow rates. It was concluded that (1) the salivary flow was dependent on body weight in duodenal ulcer patients as well as in controls, and (2) although salivary gland hyperplasia could be postulated in duodenal ulcer patients on the basis of increased salivary flow, the latter was poorly related to maximal acid secretion and therefore, if a combination of parietal cell and salivary gland hyperplasia did exist, it should be considered as incidental.